2010
DOI: 10.1002/jor.21225
|View full text |Cite
|
Sign up to set email alerts
|

An injectable composite material containing bone morphogenetic protein‐2 shortens the period of distraction osteogenesis in vivo

Abstract: To investigate new methods that can decrease the duration of bone transport (BT) distraction osteogenesis, we injected composite materials containing recombinant human bone morphogenetic protein-2 (BMP-2) and induced the generation of a callus bridge by rapid segmental transport (4 mm/day) in a rabbit bone defect model. The composite materials consisted of BMP-2 (0, 30, or 100 mg), btricalcium phosphate powder (bTCP, 100 mg/animal; particle size, <100 mm), and polyethylene glycol (PEG; 40 mg/animal). A paste o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In addition to accelerating fracture healing, bone graft substitutes may also serve as a drug delivery vehicle for various antibiotics, growth factors, and anti-osteoporosis drugs [4][5][6][7][8]. Calcium sulfate is also proposed as a carrier to deliver fibroblast growth factor and simvastatin [19,20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to accelerating fracture healing, bone graft substitutes may also serve as a drug delivery vehicle for various antibiotics, growth factors, and anti-osteoporosis drugs [4][5][6][7][8]. Calcium sulfate is also proposed as a carrier to deliver fibroblast growth factor and simvastatin [19,20].…”
Section: Discussionmentioning
confidence: 98%
“…Besides the use of different kinds of implants to hold the reduction of displaced fracture fragments during surgeries, intra-operative applications of bone grafts into bone voids are considered to support mechanical stability, or to provide structural replacement to accelerate fracture healing and promote early rehabilitation [3]. In addition to supporting mechanical stability to improve bone defect repair, bone graft substitutes also serve as a controlled drug delivery system for various purposes [4][5][6][7]. A number of studies have reported using bone substitutes to deliver antibiotics locally for open fractures, infection prevention, and osteomyelitis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the protein adsorption (e.g. growth factor) is rarely in the normal condition, but is significant in the growth of new tissue [18].…”
Section: Biomaterials For Tissue Induction and Protein Adsorptionmentioning
confidence: 99%
“…Among the various factors which can induce bone growth, bone morphogenic protein (BMP) is believed to be the primary facilitator of bone regeneration in DO. [13][14][15][16][17][18] BMP belongs to the transforming growth factor β superfamily. It promotes vascular invasion, bone formation, bone remodeling, and bone marrow differentiation by directing cell differentiation of mesenchymal stem cells to become osteoblasts and osteocytes, which in turn build and renew the extracellular matrix.…”
mentioning
confidence: 99%
“…rhBMP-2 is known to enhance consolidation, shorten the period of distraction, and eventually accelerate bone regeneration. 13,16,17,22,23 We used a specially designed drug-delivering distraction device for periodic injection of rhBMP-2 during TDO.…”
mentioning
confidence: 99%